Microphysics of Clouds and Precipitation - Pruppacher, H.R.; Klett, J.D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This book provides the most comprehensive treatment to date of the microphysical processes which lead to cloud and precipitation formation. Emphasis is placed on presenting a quantitative description of the various mechanisms (e.g. nucleation, diffusional growth and evaporation, collisional growth and breakup) which lead to the formation of cloud and precipitation particles, individually and in populations. The second edition of this highly acclaimed book has been extensively updated to incorporate new research reported in a large number of articles and dozens of books and conference proceedings published since the first edition. Some highlights include: a new chapter on cloud chemistry; improved statistical mechanics models for homogeneous and heterogeneous ice nucleation; better data on aerosol size distribution and on fundamental properties of water; new data and models for asymmetric flow past particles of various shapes and for drop oscillation and breakup; extended treatment of drop coalescence and particle collision cross-sections, including some new effects of turbulence; more complete simulations of stochastic growth; expanded treatment of growth modes of graupel, rime and hailstones; new field data and modelling concerning effects of electric fields and charges on cloud microphysics. Audience:The book is directed primarily at undergraduate and graduate level students of cloud physics, as well as at specialists in the field of aerosol physics, cloud dynamics, climate modelling, air chemistry, air pollution, and weather modification.
Historical Review -- Microstructure of Atmospheric Clouds and Precipitation -- The Structure of Water Substance -- Equilibrium Between Water Vapor, Water, Aqueous Solutions, and Ice in Bulk -- Surface Properties of Water Substance -- Equilibrium Behavior of Cloud Drops and Ice Particles -- Homogeneous Nucleation -- The Atmospheric Aerosol and Trace Gases -- Heterogeneous Nucleation -- Hydrodynamics of Single Cloud and Precipitation Particles -- Mechanics of the Atmospheric Aerosol -- Cooling of Moist Air -- Diffusion Growth and Evaporation of Water Drops and Snow Crystals -- Cloud Particle Interactions -- Growth of Cloud Drops by Collision, Coalescence and Breakup -- Growth of Ice Particles by Accretion and Ice Particle Melting -- Cloud Chemistry -- Cloud Electricity.
Keywords: Geography; Meteorology; Earth Sciences; Meteorology/Climatology.